A Preliminary Investigation Examining the Use of Minor Discipline Referral Data to Identify Students at Risk for Behavioral Difficulties: Observations Within Systems of Schoolwide Positive Behavior Interventions and Supports. Issue 4 (1st October 2016) - Cavanaugh, Brian
ABSTRACT: Within multitiered behavioral frameworks such as schoolwide positive behavior interventions and supports (SWPBIS), it is recommended that schools use multiple sources of data to identify students at risk who may benefit from additional intervention. To date, much of the research in this area has focused on examining either systematic screening data or major office discipline referrals. This study adds to the literature on this topic by examining the extent to which data collected on minor behavior problems may make useful contributions towards identifying students at risk. Using a sample of 597 elementary school students, descriptive and inferential statistical data indicate that minor discipline data may be a useful additional piece of information for schools to consider when screening students for behavioral risk. Additional research is needed to confirm this finding. Implications for practice and research are discussed.